PERANCANGAN SISTEM PAKAR DIAGNOSA PENYAKIT ISPA DENGAN METODE CERTAINTY FACTOR BERBASIS ANDROID - Laila Septiana (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2016)
The use of information technology for the purposes of access to information is now widely popular in the community, including use for accessing health information. Acute respiratory infection, or often referred to as ISPA is the occurrence of severe infection in the sinuses, throat, airways or lungs. Infections that occur more often caused by a virus although the bacteria can also cause this condition. Checking the symptoms of this disease carried by medics, in this case, the doctor. In the present study, researchers will build an expert system using forward search method (Forward Chaining) to find a solution or the possibility of the disease suffered by the user and using certainty factor to gain confidence the percentage of the illness. This Expert System Applications produce the output of the possibility of Upper Respiratory Infection (ARI) suffered by symptoms felt by the user.